Genome-wide identification analysis in wild-type Solanum pinnatisectum reveals some genes defending against Phytophthora infestans - Shen, Chunxiu; Lu, Qineng; Yang, Di; Zhang, Xueru; Huang, Xinping; Li, Rungen; Que, Zhiqun; Chen, Na (Frontiers in Genetics, 2024)
Solanum Pinnatisectum exhibits strong resistance to late blight due to Phytophthora infestans, but only an incomplete genome assembly based on short Illumina reads has been published.In this study, we generated the first chromosome-level draft genome for the wild-type potato species S. Pinnatisectum in China using Oxford Nanopore Technology (ONT) sequencing and Hi-C technology. The high-quality assembled genome size is 664 Mb with a scaffold N50 value of 49.17 Mb, 65.87% of which was occupied by repetitive sequences, and long terminal repeats (LTRs) were predominant (42.51% of the whole genome). The genome of S.Pinnatisectum was predicted to contain 34,245 genes, and 99.34% of which were functionally annotated. Moreover, 303 NBS-coding disease resistance (R) genes were predicted in the S.Pinnatisectum genome to investigate potential mechniasms of late blight disease resistance.The high quality chromosome-level reference S. Pinnatisectum genome may provide potential valuable resources for intensively and effectively investigating molecular breeding and genetic research in the future.